Electrical impedance tomography for lung ventilation monitoring of the dog - Gloning, Simon; Pieper, Korbinian; Zoellner, Martin; Meyer-Lindenberg, Andrea (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2017)
Background: Electrical impedance tomography (EIT) is a radiation free technique which takes advantage of the different electrical conductivities of different tissues. Its main field of application is lung ventilation monitoring. The aim of this prospective study was to evaluate the feasibility of collecting EIT information on a sample of dogs with different thoracic shapes under clinical conditions by connecting an electrode belt without fur clipping. Material and methods: Fifteen pulmonary healthy dogs were anaesthetized, positioned in sternal recumbency and ventilated in a pressure-controlled mode at three different positive end-expiratory pressure levels (PEEP) of 0, 5 and 10 cmH2O for five breaths each, with a peak inspiratory pressure of 15 cmH2O. The impedance changes were recorded with a commercial EIT device applied around the thorax. Subsequently, the ventilation regi me was repeated and a computed tomography scan (CT) of the same thoracic segment was performed for each PEEP level. The tidal volume (Vt) was recorded. For the collection of EIT data the sum of regional impedance changes was recorded. The impedance value of the entire lung (global) was recorded and the ventilated area was quartered into four regions of interest (ROI). In a CT image with the fewest adjacent organs, lung tissue was selected to obtain the mean value of lung radiodensitiy in Hounsfield-Units (HU) for the entire lung and for the four ROIs. Results: EIT recordings via the electrode belt were possible without clipping. There was a significant correlation for the parameters of aeration as measured by EIT and CT for both the entire ventilated lung and the corresponding ROIs. The increasing PEEP resulted in a proportional increase of the impedance, and there was a negative correlation between EIT and Vt. The better ventilated dorsal ROIs could be identified using both EIT and CT. An intra-assay coefficient of variation showed a good reproducibility for lung ventilation in anaesthetized dogs in the EIT. Discussion: The results show that EIT is a reliable method for evaluating the ventilation of dogs in a clinical setting. The accuracy of EIT might be improved by using a mesh corresponding to the different thoracic shapes of the dogs.
Keywords: Lung function; general anaesthesia; positive end-expiratory pressure